RASIO T4 DAN T3 DI DALAM CAIRAN FOLIKEL OVARIUM KECIL DAN SERUM DARAH SAPI POTONG - , MELINA MIRMASARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Thyroid hormone is a hormone that have functions to control the growth, differentiation and metabolism of virtually all somatic tissues. Abnormal levels of thyroid hormone will cause infertility or reduced reproductive function. One of speculated roles of thyroid hormones curently under review is the direct regulation of steriodogenesis within the ovarian follicular cells by the hormone. The aims of the study to determine the ratio hormones of T4 and T3 in bovines follicular fluid and serum. This study used five beef cattles that have small ovarian follicles (< 5 mm) to be cut in Rumah Pemotongan Hewan Giwangan. Blood samples were taken from the jugular vein before the cattles were cut and small follicular fluid samples taken after the cattles ware cut then examined using a commercial ELISA kit for each samples. The results of the study showed that the ratio of hormones T4 and T3 in follicular fluid 10.74 Â± 2.00 Î¼g/ml, whereas the ratio of hormones T4 and T3 in serum 16.71 Â± 3.57 Î¼g/ml. Results of statistical analysis showed that there were significant differences between the average ratio of hormones T4 and T3 in follicular fluid of small ovarian follicles and serum of beef cattles, so it can be concluded that ratio of T4 and T3 in the blood serum can not to be used as a parameter to the ratio of T4 and T3 in follicular fluid of small ovarian follicles. Keywords : follicular fluid of small ovarian follicles, beef cattle, serum, ratio, thyroxine, triiodothyronine.